Coexistence of chronic lymphocytic leukaemia and polycythemia vera - Beyler, Ozlem; Demir, Cengiz (Archive of Oncology, 2025)
We report a rare case of coexistence of chronic lymphocytic leukaemia (CLL) and polycythemia vera (PV) in a patient initially diagnosed and treated for CLL. A 61-year-old man presented with fatigue and night sweats, with laboratory tests showing elevated haemoglobin, hematocrit (HCT), leukocyte count and splenomegaly. Peripheral blood smear revealed lymphocytosis with basket cells, and flow cytometry confirmed CLL (RAI stage II). FISH analysis was negative for del13q, del11q, trisomy 12, del 17p and del6q. Chemotherapy was started because of B symptoms. Persistent splenomegaly and elevated HCT at follow-up prompted further evaluation, which revealed a JAK2 V617F mutation and an erythropoietin (EPO) level
Keywords: Chronic Lymphocytic Leukaemia, Polycythemia Vera, JAK2 V617F mutation, germline mutations